Elaboration of Lutein‐Loaded Nanoliposomes Using Supercritical CO2. Issue 4 (26th February 2021) - Martino, Mathieu; Mouahid, Adil; Trucillo, Paolo; Badens, Elisabeth
Abstract: A batch process for producing lutein‐loaded liposomes using supercritical CO2 is studied. The effects of the variation of pressure (10 and 15 MPa), temperature (308, 313, and 318 K), and lutein to lipid ratio (0.5 and 1 wt%) on the liposome average size and size distribution are investigated, as well as on the encapsulation efficiency (EE) of lutein. This process is worked in a repeatable manner and is allowed the production of nanoliposomes with mean diameters (MDs) ranging from 65 ± 33 to 77 ± 40 nm, obtaining lutein EEs ranging from 82.1 ± 3.7% to 91.9 ± 2.9%. Temperature, pressure, and lutein to lipid ratio seem to have no impact on size, size distribution, and EE on formed liposomes. The use of low temperatures and low pressures allows the obtainment of liposomes with diameters less than 100 nm and limits the process energy cost. Moreover, the supercritical CO2 ‐assisted batch process effectively encapsulates lutein into liposome, an antioxidant molecule used for the prevention of retinal damage. Liposomes formed by this supercritical process have the desired characteristics for human target delivery. Practical applications: This work on the optimization of a process for developing liposomes in a supercritical environment has applications in medicine. Indeed, the liposomes formed with this process are nanoliposomes with a size of less than 80 nm. In addition, excellent lutein EEs (hydrophobic molecules) show that the liposomes formed constitute excellent coating matrices for the protection of active ingredients. These reasons make these liposome matrices applicable in nanomedicine (injection of sensitive drugs requiring protection before injection). The elaboration process also makes it possible to form liposomes with desired properties by changing pressure, temperature, or lecithin concentration. Therefore, this work focuses on the properties of liposomes as a function of the operating conditions. Abstract : Liposomal nanoencapsulation of lutein is realized using a batch supercritical CO2 process. Nanoliposome formation occurs during the depressurization of CO2 /water (or water/CO2 ) emulsion made under supercritical conditions. Liposomes characteristics (size and size distribution) and encapsulation efficiency (EE) can be controlled by process operating conditions (pressure, temperature and drug to lipid ratio).